Celebrate her for the fruit of her hands: essays in honor of Carol L. Meyers - Meyers, Carol L.; Ackerman, Susan (Eisenbrauns, 2014)
Contents -- Preface -- Abbreviations -- A Select Bibliography of the Works of Carol L. Meyers -- Introduction: A Teacher and Scholarâ€?s Appreciation -- Charles E. Carter -- Introduction: A Colleagueâ€?s Appreciation -- Susan Ackerman -- Hannahâ€?s Tears -- Susan Ackerman -- Women, Law, and Legal Procedure in Ancient Israel -- James P. Ashmore -- Nationalist Narratives and Biblical Memory -- Cynthia M. Baker -- When It Both Is and Is Not Rape: Gender Constructions in 2â€S̄amuel 13:1â€?22 -- Karla G. Bohmbach